1997
DOI: 10.1148/radiology.204.2.9240548
|View full text |Cite
|
Sign up to set email alerts
|

Malignant esophageal fistulas and perforations: management with plastic-covered metallic endoprostheses.

Abstract: Covered metallic stents offer effective treatment for perforations and fistulas in patients with esophageal malignancy. Patients with recurrent fistulas can be treated with additional stents. Fistulas close to the upper esophageal sphincter may be closed with placement of parallel covered metallic stents in the esophagus and trachea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0
5

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(81 citation statements)
references
References 0 publications
1
75
0
5
Order By: Relevance
“…Stent placement for esophagorespiratory fistulas. Placement of a covered metal stent is the treatment of choice for esophagorespiratory fistulas [21][22][23][24][25]. Complete sealing of a fistula can be established in more than 90% of patients with no clear difference between the presently available covered metal stents.…”
Section: Consmentioning
confidence: 99%
“…Stent placement for esophagorespiratory fistulas. Placement of a covered metal stent is the treatment of choice for esophagorespiratory fistulas [21][22][23][24][25]. Complete sealing of a fistula can be established in more than 90% of patients with no clear difference between the presently available covered metal stents.…”
Section: Consmentioning
confidence: 99%
“…These forms of treatment have low success rates and most patients undergo gradual deterioration as a result of undemutrition and sepsis. Several authors have recently reported high success rates following closure of perforations using covered metallic stents [2][3][4][5]. We recently encountered a patient with a perforation that could not be closed by a standard covered Wallstent endoprosthesis because the upper esophagus was dilated as a result of esophageal obstruction.…”
mentioning
confidence: 99%
“…In 80% of cases, after placement of the stent there is complete closure of the fistula, nevertheless complications are familiar [2] ; which comprise of unrelenting chest pain, tracheal or esophageal mucosa necrosis due to pressure, development of granulation tissue causing stenosis, dyspnoea due to compression of the trachea, perforation, hemorrhage (which may be apparent as hemoptysis or hematemesis) and stent migration. Incidence of stent migration is 5% to 15% and urgent necessity for stent replacement [3,9,10] ; with these logistics, tumor in-growth through the stent metal in majority of patients with malignant esophageal fistulas covered stents are used as the cover prevent mesh [11] .…”
Section: Discussionmentioning
confidence: 99%